Role of Berberine on molecular markers involved in migration of esophageal cancer cells - Mishan, M A; Ahmadiankia, N; Matin, M M; Heirani-Tabasi, A; Shahriyari, M; Bidkhori, H R; Naderi-Meshkin, H; Bahrami, A R (Cellular and Molecular Biology, 2015)
Berberine is an isoquinoline alkaloid found in several plant species like famous chinese herb, Rhizoma coptidis which has been used locally as a strong gastrointestinal remedy for thousands of years. The inhibitory effects of berberine on tumor progression properties have been reported before. In this study, we investigated the effect of berberine on an esophageal cancer cell line, KYSE-30 with emphasis on its effects on the expression of certain chemokine receptors. The cytotoxic effect of berberine on KYSE-30 cells was analyzed by MTT assay. In vitro cell migration assay was also applied to the treated cells and the expression levels of the selected chemokine receptors (CXCR4 and CCR7) was measured at mRNA level. A retarded growth, associated with increasing concentrations of berberine, was obvious. On the other hand, the migration rate of the cells was decreased when they were treated with different concentrations of berberine and the expression levels of the two chemokine receptors, involved in the migration and metastasis of esophageal cancer cells, were decreased following the same treatments. With these results, we tend to conclude that berberine might be a proper candidate for further investigations, by targeting the chemokine receptors, and possible applications as anti-metastatic agent in cancer studies.